Boosting Electroreduction Kinetics of Nitrogen to Ammonia via Atomically Dispersed Sn Protuberance. Issue 13 (20th February 2023) - Zhang, Lijuan; Zhou, Hanfeng; Yang, Xiaoju; Zhang, Shengbo; Zhang, Haimin; Yang, Xuan; Su, Xintai; Zhang, Jiangwei; Lin, Zhang
Abstract: Atomically dispersed metal catalysts show potential advantages in N2 reduction reaction (NRR) due to their excellent activity and efficient metal utilization. Unfortunately, the reported catalysts usually exhibit unsatisfactory NRR activity due to their poor N2 adsorption and activation. Herein, we report a novel Sn atomically dispersed protuberance (ADP) by coordination with substrate C and O to induce positive charge accumulation on Sn site for improving its N2 adsorption, activation and NRR performance. The extended X‐ray absorption fine structure (EXAFS) spectra confirmed the local coordination structure of the Sn ADPs. NRR activity was significantly promoted via Sn ADPs, exhibiting a remarkable NH3 yield ( R NH3 ) of 28.3 μg h −1 mgcat −1 (7447 μg h −1 mgSn −1 ) at −0.3 V. Furthermore, the enhanced N2 Hx intermediates was verified by in situ experiments, yielding consistent results with DFT calculation. This work opens a new avenue to regulate the activity and selectivity of N2 fixation. Abstract : An asymmetric Sn atomically dispersed protuberance (ADP) having a special coordination with substrate C and O atoms was designed. This unique structure could induce positive charge accumulation on Sn site for improving its N2 adsorption, activation and thus the N2 reduction reaction (NRR) performance. As a result, the obtained Sn ADPs displayed an outstanding electrocatalytic activity, high selectivity stability, and durability in the NRR.